2007
DOI: 10.1002/prot.21400
|View full text |Cite
|
Sign up to set email alerts
|

Drug block of the hERG potassium channel: Insight from modeling

Abstract: Many commonly used, structurally diverse, drugs block the human ether-a-go-go-related gene (hERG) K(+) channel to cause acquired long QT syndrome, which can lead to sudden death via lethal cardiac arrhythmias. This undesirable side effect is a major hurdle in the development of safe drugs. To gain insight about the structure of hERG and the nature of drug block we have produced structural models of the channel pore domain, into each of which we have docked a set of 20 hERG blockers. In the absence of an experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
122
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(138 citation statements)
references
References 74 publications
(160 reference statements)
13
122
3
Order By: Relevance
“…It has previously been suggested that the inner (cytoplasmic) half of the S6 helices of Kv11.1 channels (Gly-648 to Tyr-667) undergoes a rotation at some point during the transition between open and inactivated states and that this rotation enhances sensitivity to block by some drugs (48,49). Whether a similar rotation or a distinct conformational change occurs in the upper (extracellular) half of the S6 helix (Phe-640 to Ile-647) remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been suggested that the inner (cytoplasmic) half of the S6 helices of Kv11.1 channels (Gly-648 to Tyr-667) undergoes a rotation at some point during the transition between open and inactivated states and that this rotation enhances sensitivity to block by some drugs (48,49). Whether a similar rotation or a distinct conformational change occurs in the upper (extracellular) half of the S6 helix (Phe-640 to Ile-647) remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…5,14 The short pore helix, the selectivity filter, and the innermost S6 helices lining the pore can, however, be confidently aligned on the basis of conservation of the filter region and a glycine hinge in S6. 15,16 The situation is more ambiguous for the S5 helices that pack against the S6 helices in the tetrameric structure, and several alignments of S5 against K + channels of known structure have been published. 15À18 We have recently reported an analysis of seven different alignments and 3D pore models utilizing conventional 3D structure quality validation methods as well as molecular dynamics (MD) simulations.…”
mentioning
confidence: 99%
“…The binding site was defined following the definition of Stansfeld et al, [19] namely as all protein atoms within 20 Å from the natural K + ion S cav . This ion is not present in the structure, but coordinates were retrieved from backbone overlay of the selectivity filter of KcsA crystallized subunit including K + ions (pdb entry: 1k4c) and our target structure.…”
Section: Dockingmentioning
confidence: 99%